Pengembangan bahan ajar berpikir komputasional berbasis bebras pada pembelajaran matematika di kelas 5 SD - Lilis Halimatusyadiyah; Dindin Abdul Muiz Lidinillah; Erwin Rahayu Saputra (IKIP Siliwangi, 2025)
Abstract Problem-solving is a crucial skill for students, especially in the rapidly evolving educational landscape. With the ongoing transition from the industrial revolution 4.0 to 5.0, computational thinking has become increasingly vital, as it underpins effective problem-solving abilities. Bebras, an international initiative, plays a key role in promoting computational thinking among students, fostering both interest and skills in this area. Bebras challenges are particularly aligned with mathematics, incorporating elements of logic, problem-solving, and recognition of patterns and structures. Given this synergy, this study aims to develop teaching materials that integrate computational thinking concepts, inspired by Bebras, into mathematics education for fifth-grade students, specifically focusing on the topic of flat shapes. The research employs the Educational Design Research (EDR) method, following the McKenney & Reeves model. Data collection was conducted through a combination of observations, interviews, questionnaires, documentation studies, and expert judgment. The findings indicate that the developed teaching materials not only enhance students problem-solving abilities but also significantly boost their engagement and interest in mathematics. These results underscore the potential of integrating computational thinking into mathematics education to better equip students with the skills needed for future challenges. Keywords: computational thinking; Bebras; problem-solving